Ventricular Myocardial Deformation in Fetuses With Tetralogy of Fallot: A Necessary Field of Investigation - Song, Xiaoyan; Cao, Haiyan; Hong, Liu; Zhang, Li; Li, Meng; Shi, Jiawei; Liu, Juanjuan; Ma, Jing; Cui, Li; Zhang, Yi; Li, Yuman; Lv, Qing; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Tetralogy of Fallot (TOF) is one of the most common cyanotic congenital heart defects (CHDs). The patterns of fetal myocardial deformations in TOF have not been well-studied. This study aimed to assess biventricular myocardial deformations in fetuses with TOF compared with normal fetuses. Methods: A retrospective cohort study of fetuses with TOF and gestational age (GA)-matched controls was conducted at a single tertiary referral center from 2014 to 2020. All enrolled fetuses underwent detailed echocardiography, and four-chamber video-clips were recorded and analyzed offline for deformation assessment by using two-dimensional speckle tracking echocardiography (2D-STE). Comparisons for baseline characteristics, cardiac morphological measurements (ventricular, atrial, and great arterial diameters or ratios, global sphericity index), systolic function parameters [ejection fraction (EF), fractional area change (FAC)], and strain parameters [global longitudinal strain (GLS), global longitudinal strain rate in systole and diastole (GLSRs, GLSRd)] were performed between fetuses with TOF and GA-matched controls. Results: Fifty-two fetuses with TOF and 52 GA-matched controls were enrolled in this study. Fetuses with TOF exhibited similar left ventricular (LV) EF (58.51 ± 5.11% vs. 57.59 ± 5.38%, P = 0.16) and right ventricular (RV) FAC (43.64 ± 2.89% vs. 44.27 ± 3.04%, P = 0.25), compared to normal fetuses. While, in deformational analysis, TOF fetuses demonstrated significantly lower LV and RV GLS values (−22.57 ± 2.91% vs. −27.39 ± 4.38%, P < 0.001 for LV GLS; −24.27 ± 3.18% vs. −28.71 ± 4.48%, P < 0.001 for RV GLS). Both LV GLS (r = −0.518, P < 0.001) and RV GLS (r = −0.534, P < 0.001) were found negatively correlated with the aortic valve-to-pulmonary valve diameter ratio (AV:PV ratio). Z-scores of PV annulus and main pulmonary artery (MPA) also had positive correlation with LV and RV GLS, respectively. Conclusions: Decreased biventricular myocardial deformations can appear even in fetuses with TOF with normal systolic ventricular function. Both LV and RV GLS values are correlated with the severity of right ventricular outflow tract obstruction. It indicates 2D-STE may be a more sensitive tool to assess fetal cardiac function than the conventional echocardiographic methods.